2002
DOI: 10.1002/path.1242
|View full text |Cite
|
Sign up to set email alerts
|

Mutated p53 as a molecular marker for the diagnosis of head and neck cancer

Abstract: In total, 10-30% of patients with head and neck squamous cell carcinoma (HNSCC) develop local recurrences despite seemingly adequate tumour resection. This may result from minimal residual cancer (MRC): small numbers of tumour cells left behind in the surgical margins, undetectable by routine histopathology. In recent studies, p53 mutations have been considered as selective and sensitive DNA markers of cancer cells. There are two potential problems in using mutated-p53 DNA as a marker. Firstly, p53 mutations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(108 citation statements)
references
References 14 publications
1
103
0
4
Order By: Relevance
“…Mutations of p53 or p53 oncoprotein are relatively late events in carcinogenesis (42,43), so, despite their biological plausibility as cancer predictors, they are insufficient for risk assessments for SCC in the UADT. Because aberrant DNA methylation usually precedes neoplastic transformation, qualitative studies have suggested that the presence of methylated genes may increase in a sequence from normal mucosa to precursor lesions to SCC (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of p53 or p53 oncoprotein are relatively late events in carcinogenesis (42,43), so, despite their biological plausibility as cancer predictors, they are insufficient for risk assessments for SCC in the UADT. Because aberrant DNA methylation usually precedes neoplastic transformation, qualitative studies have suggested that the presence of methylated genes may increase in a sequence from normal mucosa to precursor lesions to SCC (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…The mutational status of TP53 in the tumors was determined by direct DNA sequencing essentially as previously described. 24 …”
Section: High-risk Hpv Rna Detectionmentioning
confidence: 99%
“…Alterations in p53 have commonly been found in HNSCCs, but its influence on prognosis remains controversial. In recent reports, p53 mutations, detected by molecular assays such as DNA sequencing, LigAmp assay, and real-time PCR, were considered a useful prognostic factor [9][10][11][12]. However, we previously reported that the IHC assay of p53 was not useful in predicting the prognoses of patients undergoing chemoradiation therapy [13].…”
Section: Discussionmentioning
confidence: 99%